Demographic pattern of weight control behaviours of Rivers State karate athletes - Elendu, I. C. (Journal of Physical Education and Sport, 2011)
Purpose: The study aimed to find out the demographic pattern of weight control behaviours of Rivers state karate athletes. Material and Method: A structured questionnaire was used to collect data from eighteen karate athletes. The data generated were analyzed using percentage and chi-square statistics. Results: It was found that majority of the karate athletes participate in weight training/exercise programme, decreased their expenditure of calories, increased their fluid intake, eat excess food and increased their consumption of calories in order to gain weight. It was found that majority of the athletes decreased their consumption of calories, and increased their expenditure of calories through exercise, restrict food intake, dehydrate, and over-exercise to lose weight. Higher proportion of the male athletes engage in weight gain behaviours than the female karate athletes, while higher proportion of female karate athletes engage in weight loss behaviours than their male counterparts. Again, greater percentage of the athletes aged 25 years and above engage in weight gain, and weight loss behaviours than their counterparts who are less than 25 years. The study showed that greater proportion of the athletes with less than 2 years of sporting experience engage in weight gain, and weight loss behaviours than karate athletes with 2 years and above as their years of sporting experience. Conclusion: Gender, age, and years of sporting experience had no significant influence on the pattern of weight gain, and weight loss behaviours of karate athletes. As a form of intervention, necessary recommendations were made.